2010
DOI: 10.1177/0011128710372196
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Effects of Violent Victimization, Violent Behavior, and Gun Carrying for Minority Inner-City Youth Living in Extreme Poverty

Abstract: sample of high school students (CDC, 2007). In addition, Cook and Laub (2002) noted that use of guns in homicides after the peak in youth violence in the early 1990s has dropped very little during the late 1990s and gun use in homicides has increased for several types of homicides (felony-type and gang related) during the late 1990s. As a result, the Centers for Disease Control has advocated for the reduction and/or elimination of gun carrying among youth to prevent firearm injuries and fatalities, which would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 38 publications
4
59
0
2
Order By: Relevance
“…The effect sizes for the latter (e.g. Bolland, 2013 andHemenway et al 2011, reported odds ratios of 4.70 or greater) were typically stronger than for the former (usually up to an odds ratio of 2: McVie, 2010;Saukkonen et al 2016).…”
Section: Interpersonal Risk Factorsmentioning
confidence: 93%
See 1 more Smart Citation
“…The effect sizes for the latter (e.g. Bolland, 2013 andHemenway et al 2011, reported odds ratios of 4.70 or greater) were typically stronger than for the former (usually up to an odds ratio of 2: McVie, 2010;Saukkonen et al 2016).…”
Section: Interpersonal Risk Factorsmentioning
confidence: 93%
“…Secondly, Spano and Bolland (2013) found that controlling for baseline violent victimisation neutralised any statistically significant relationship between baseline violent offending and gun-carrying at one-year follow-up. However, a more complex analysis in their later paper (Spano et al 2012), which accommodated victim-offender overlap, reversed the findings and gave greater weight to violent offending as an explanation of weapon-carrying.…”
Section: Individual-level Risk Factorsmentioning
confidence: 94%
“…Youth and young adults are more likely to carry guns illegally when engaged in the drug trade (Sheley & Wright, 1993;Lizotte et al, 1997Lizotte et al, , 2000, because their friends carried a gun (Sheley & Wright, 1993;Sheley & Brewer, 1995;Webster, Gainer, & Champion 1993;Lizotte et al, 1997), in the commission of a crime (Sheley & Wright, 1993;Sheley & Brewer, 1995), and when they have an arrest record (Webster et al, 1993). Violent behavior and victimization each have strong connections to illegal gun carrying (Spano & Bolland, 2013;Spano, Pridemore, & Bolland, 2011). Exposure to violence can also include acquiring a gun due to a perceived need for protection (Sheley & Wright, 1993;Sheley & Brewer, 1995;Spano et al, 2011;Spano & Bolland, 2013).…”
Section: Risk Factors Of Illegal Gun Carryingmentioning
confidence: 99%
“…Violent behavior and victimization each have strong connections to illegal gun carrying (Spano & Bolland, 2013;Spano, Pridemore, & Bolland, 2011). Exposure to violence can also include acquiring a gun due to a perceived need for protection (Sheley & Wright, 1993;Sheley & Brewer, 1995;Spano et al, 2011;Spano & Bolland, 2013). Gang membership has also been shown to consistently be a correlate of illegal gun carrying (Lizotte et al, 1997(Lizotte et al, , 2000Bjerregaard & Lizotte, 1995;Decker, Pennell, & Caldwell, 1996;Bennett & Holloway, 2004;Luster & Oh, 2001;Hayes & Hemenway, 1999).…”
Section: Risk Factors Of Illegal Gun Carryingmentioning
confidence: 99%
See 1 more Smart Citation